Presacral immature teratoma with carcinoid in a young adult male: A rare case presentation - Kaur, Kanwardeep; Nibhoria, Sarita; Kaur, Manmeet; Kaur, Arshpreet (Indian Journal of Case Reports, 2017)
Presacral region is defined as potential space delineated by the rectum anteriorly, sacrum posteriorly, peritoneal reflection superiorly, and perineal muscles inferiorly. Tumors within the presacral space are uncommon with an incidence of 1:40,000. Presacral teratomas in adults are very rare. We, herein, present a case of 39?year?old male who was admitted with chief complaint of per rectal bleed. A large presacral mass was present which on histopathological examination was found to be immature teratoma with neuroendocrine differentiation.